Signal conditioning and computer interface for a low cost portable fibre optic sensor: (software and hardware development) / Mazlan Abdul Moin - Abdul Moin, Mazlan (1998)
On-line measurement and monitoring system is an important criteria in the present industrial and environmental measurement application. Thus, interfacing an instrument to a data acquisition system is one of the main issue. This project describes some considerations about the concept and implementation in the design of fiber optie sensor to sense and measure colors and displacements using computer. A signal conditioning circuitry is developed to obtain an optimum resolution. It also described general view of the C / C++ software programming design. PICO-ADC11 is used as interfacing between the hardware and computer by using parallel port or printer port. The system is able to interprete the signals from optica] fiber sensor instrument that record and display the measurands (colours and displacement) continuously. The actual colour can be displayed using look-up table and the displacement measurement can be achieved with a Standard deviation of ± 0.05 micrometer